TRANSFORMASI PEMBELAJARAN IPA MELALUI IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS WEB UNTUK PENGUATAN LITERASI SAINS SISWA SEKOLAH DASAR - Amanda P.D Manalu; Juliana br Sihombing; Atania Rosbina Br Bangun; Suryani; Nurhayati (STKIP Subang, 2026)
SDN 060914 Medan Sunggal faced challenges in science learning, particularly in teaching the Earth's layer structure, due to limited utilization of digital learning media and the difficulty of visualizing abstract concepts. This community service program aimed to implement a research-based web learning medium to support science instruction and strengthen students' science literacy. The program involved one fifth-grade teacher and 28 students through a participatory approach consisting of needs assessment, teacher training, classroom implementation, mentoring, and evaluation. Data were collected through observations, interviews, questionnaires, and documentation. The results showed that the teacher was able to independently operate and integrate the web-based learning medium into classroom learning after participating in the training and mentoring activities. Students demonstrated high participation in utilizing the medium, with active engagement increasing from 52.4% to 85.7% during the implementation period. In addition, 89.3% of students stated that the medium helped them understand the Earth's layer structure material more easily. The program contributed to improving teachers’ capacity in utilizing digital learning media and supported more interactive science learning. The implementation of the web-based learning medium can serve as an alternative strategy for strengthening digital-based science learning in elementary schools..